2019
DOI: 10.1002/aur.2108
|View full text |Cite
|
Sign up to set email alerts
|

A non randomized mentalization intervention for parents of children with autism

Abstract: Parents of children diagnosed with autism spectrum disorder (ASD) report higher levels of stress and other negative affective states than parents of typically developing children. One important resource in managing these heightened levels of negative affect is emotion regulation, which in turn depends upon the ability to recognize and understand one's own and others' mental states (referred to as mentalization or reflective functioning). In this study, parents of children with ASD either participated in a ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
(80 reference statements)
1
27
0
2
Order By: Relevance
“…Byrne and colleagues (2019) reported that parents showed no significant improvement in parental mentalizing capacity following completion of the 20-session Lighthouse programme. In contrast, Enav and colleagues (2019) found that the intervention group demonstrated a significant improvement in RF at treatment end ( p = .0002). This was the only study that focused on parents of children with neurodevelopmental delays.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Byrne and colleagues (2019) reported that parents showed no significant improvement in parental mentalizing capacity following completion of the 20-session Lighthouse programme. In contrast, Enav and colleagues (2019) found that the intervention group demonstrated a significant improvement in RF at treatment end ( p = .0002). This was the only study that focused on parents of children with neurodevelopmental delays.…”
Section: Resultsmentioning
confidence: 68%
“…Adkins and colleagues (2018) noted a significant interaction effect on three of the five subscales of the Parenting Stress Index (Abidin, 1995) with moderate effect sizes noted. Enav et al (2019) reported no difference in parents’ emotional regulation capacity following treatment, however, parents’ sense of self-efficacy showed a significant improvement with small effect sizes noted ( d = .37). Midgley et al (2019b) reported significant reductions in total parenting stress ( d = .56) but non-significant improvement in parental self-efficacy.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In future studies, it will be important to assess the association between variation in PRF and child-level outcomes in both ASD and typically developing children. Given that reflective functioning has been found to improve with intervention (Enav et al, 2019), it will be interesting to see whether a parental intervention to improve reflective functioning would be successful to support the typically developing siblings’ emotional adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The current study was a part of a 4-week, non-randomized controlled intervention designed for parents of children with ASD (Enav et al, 2019).…”
Section: Methodsmentioning
confidence: 99%